The Interplay Between Technology and Motivation in EFL L2 Classrooms: A Systematic Review of 2019–2024 Research - Annishah; Lailatun Nisvi Rizki Amalia; Utami Widiati; Anik Nunuk Wulyani (VELES Voices of English Language Education Society, 2025)
Motivation is a key determinant of success in second language (L2) learning, and technology has emerged as a crucial factor in fostering motivation for English as a Foreign Language (EFL) students. A systematic synthesis of recent evidence remains scarce despite extensive research, particularly in light of technological advancements between 2019 and 2024. This study employed a systematic literature review (SLR) following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol to ensure methodological transparency and replicability. Six major databases (Google Scholar, Taylor & Francis, ProQuest, Wiley, Sage Pub, and Cambridge Core) were systematically searched using predefined keywords. The initial search yielded 50 peer-reviewed empirical studies published between 2019 and 2024; after applying stringent inclusion, exclusion, and quality assessment criteria, 26 eligible studies were analyzed. Data extraction and synthesis focused on four research questions: (1) research methods employed, (2) motivational frameworks used, (3) impacts of technology on motivation, and (4) technology tools that enhance motivation. Findings indicate a dominance of experimental (38.5%) and mixed-methods (26.9%) designs, with the socio-educational framework most frequently adopted, followed by self-determination theory, ARCS, and cognitive models. Technology shows a predominantly positive impact on motivation, with visual-based tools (AR/VR), social media-based platforms, and game-based applications demonstrating strong motivational benefits. However, effects vary by context and learner proficiency. A few studies report neutral or negative impacts, particularly with online platforms. This review highlights methodological gaps, calling for more longitudinal and mixed-methods research to explore contextual and long-term motivational effects, and provides evidence-based recommendations for selecting effective technology tools in EFL classrooms.